A study on role of magnetic resonance imaging in the evaluation of intracranial neoplastic lesions - Halli, Shekavva; Hegde, Vinod (International Journal of Research in Medical Sciences, 2023)
Background: Neoplastic central nervous system (CNS) lesions are a heterogeneous group of diseases with a variable outcome that reflects the precision of diagnosis and the delivery of optimal and specific treatment. CNS imaging has a pivotal role in directing management decisions. In the present study, cases of either clinically suspected intracranial neoplastic lesions or already diagnosed cases of neoplastic lesions were studied by cross sectional imaging of magnetic resonance imaging (MRI). Methods: In this prospective study, 30 cases of intracranial neoplastic lesions were studied by 1.5T Siemens Essenza MR scanner over a period of 6 months. Imaging findings were evaluated and tabulated. Results: Total 30 cases of in intracranial neoplastic lesions were studied aged between 12 to 87 years (17 men and 13 women). Most common presenting complaint was headache. Solitary lesions were present in 21 patients (70%) and multiple lesions in 9 patients (30%). 80% of the lesions were supratentorial, 13.3% were infratentorial and 6.6% were seen in both infra and supratentorial region. 76.6% were intra-axial and 23.3% were extra-axial. Metastasis were the most common neoplastic lesions; glial tumors are the second most common neoplastic lesions. Meningiomas were the most common benign tumors. Mass effect and perilesional edema were the most common associated findings. Conclusions: MRI is the first line of investigation for diagnosis and evaluation of intracranial neoplastic lesions with reasonable degree of diagnostic accuracy. Neuroimaging in combination with clinical findings can be helpful in early diagnosis and timed intervention.